Inhibitor or purchase in intention of fake drugs in Thailand: Role of spiritual, ethical, religious and moral factors. - Chaopreecha, Oranuch; Jantapo, Anchalee (International Journal of Psychosocial Rehabilitation, 2020)
The investigation of emerging customers and their needs is very crucial for the exploration of moral aspects in terms of advertisement. The basic purpose of the current study is also to find out the relationship or role of ethical concern, intrinsic and extrinsic religiosity and moral judgment on the purchase intention of the customers with the help of customer attitude as a mediating variable. The current study is designed based on a survey questionnaire. Additionally, the respondents are selected based on random as well as convenience sampling in which the respondents select from shopping malls, groceries, and streets. For all variables such as moral judgment, spirituality, intrinsic and extrinsic religious the five-item measurement scale is used. Under the analysis section, the descriptive statistics test and KMO test are applied to analyze the mean, median, and standard deviation values. Besides, the results have indicated that moral judgment, as well as intrinsic religiosity, has an insignificant impact on purchase intention while ethical concern and extrinsic religiosity have a positive impact on purchase intention. At the same time, the role of attitudes as a mediating between ethical concern and purchase intention is also insignificant. Finally, the given study is effective and beneficial for drug-making industry and the customers who want positive attitudes.